IDENTIFIKASI POTENSI BAHAYA DAN RISIKO SERTA PENETAPAN PENGENDALIAN PADA DIVISI SORTASI PT TRANSCO ENERGI UTAMA POM - Wenny Murdina Asih; Muhammad Ismael (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Accidents and occupational diseases can also result in lost revenue. Accidents and occupational diseases can be prevented if the sources of dangers that cause accidents and occupational diseases can be identified. The focus of this research is to identify hazards and risks so that appropriate controls may be determined based on the conditions of PT Transco Energi Utama POM's Sorting Division. This study was held at PT Transco Tenaga Utama POM's Sorting Division from February to October 2020. The work process, equipment, and environment around the work area are the subject of research, which involves hazard identification, risk assessment, and control determination, as well as informants. According to the results of this study, the sorting division identified 23 potential dangers, with the majority of physical hazards falling into the medium category (52.17%). All of the risk ratings are in the low range. Control of elimination, engineering control, administration, and use of Personal Protective Equipment are all examples of hazard control. The maximum level of control on the usage of Personal Protective Equipment only reaches 46.5 percent, indicating that the determination of control carried out is still inadequate. It is hoped that by developing Standard Operating Procedures and regularly reviewing the execution of work safety requirements, the amount of risk can be lowered. Developing communication regarding work safety messaging can also be used to add to the control. The company should also be able to complete the workers' PPE according to the sort of job.